1985
DOI: 10.1029/tc004i007p00739
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary normal and reverse faulting and the state of stress in the central Andes of south Peru

Abstract: Field studies in the Andes of southern Peru show that in the High Andes and Pacific Lowlands, Quaternary and Recent faults are normal. This extensional tectonics postdates compressional deformations of Pliocene‐early Quaternary age. In the sub‐Andes the observed deformations are compressional; they affect early Quaternary deposits. Some of the faults separate Quaternary deposits from the bedrock and thus are clearly of tectonic origin and not landslide effects. Striations on the fault planes indicate N–S trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 41 publications
8
96
0
1
Order By: Relevance
“…Local reverse and normal apparent surface movements are known to occur along major strike-slip faults in the forearcs of northern Chile (Victor et al, 2004) and southern Peru (Hall et al, 2012). The present-day main sinistral strike-slip kinematics of the Incapuquio fault system demonstrated by the seismicity is compatible with normal apparent displacements as observed by Schildgen et al (2009) and Sébrier et al (1985Sébrier et al ( , 1988.…”
Section: Fault Geometry and Kinematicssupporting
confidence: 67%
See 3 more Smart Citations
“…Local reverse and normal apparent surface movements are known to occur along major strike-slip faults in the forearcs of northern Chile (Victor et al, 2004) and southern Peru (Hall et al, 2012). The present-day main sinistral strike-slip kinematics of the Incapuquio fault system demonstrated by the seismicity is compatible with normal apparent displacements as observed by Schildgen et al (2009) and Sébrier et al (1985Sébrier et al ( , 1988.…”
Section: Fault Geometry and Kinematicssupporting
confidence: 67%
“…In southern Peru, the Incapuquio fault zone has a strong geomorphic imprint on the Andean range (Huaman, 1985;Sébrier et al, 1985). Based on microtectonic studies, Sébrier et al (1985Sébrier et al ( , 1988 and Schildgen et al (2009) identified different kinematic episodes.…”
Section: Fault Geometry and Kinematicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most recent eruption of Sabancaya spanned 1990-1998, following about 200 years of dormancy [Gerbe and Thouret, 2004]. The volcano is surrounded by an extensive system of active faults and lineaments (Figure 1c)-the Huambo-Cabanaconde Fault Zone to the northwest, which is composed of the Trigal and Solarpampa normal faults and minor subparallel faults; the Ichupampa normal fault to the northeast; the Pampa Sepina fault zone and Sepina lineament to the east; and the Huanca normal fault to the southwest [Sebrier et al, 1985;Mering et al, 1996;Huamán-Rodrigo et al, 1993;Macharé et al, 2003].…”
Section: Introductionmentioning
confidence: 99%